Impact before and after the Covid-19 pandemic on LQ45 stock volatility - Humera Asad Ullah Khan; Rachmad Hidayat (Technium Social Sciences Journal, 2023)
The purpose of this study was to find out the difference between LQ45 stocks before and after the COVID-19 pandemic. The period used in this study is 2019-2020 using data from 45 companies whose shares are included in the LQ45 group listed on the Indonesia Stock Exchange. The data in this study were processed using IBM SPSS version 25 with a different test model (compare means paired samples t-test). It is found if there is a difference in the situation before and after the COVID-19 pandemic in the volatility of the price of the LQ45 shares listed on the Indonesia Stock Exchange. In general, there was a decrease of -6.14% after the incident in 2020 compared to before the COVID-19 pandemic situation occurred in 2019. There were 13 companies or reached 28, there were as many as 32 companies, or as much as 71.11 percent whose share value decreased. Issuers with the core business of national television, mining, pulp, distributor of heavy equipment, communication equipment, construction, some banking, spinning and weaving, and animal feed can be a choice for future investment.